2002
DOI: 10.1074/jbc.m109212200
|View full text |Cite
|
Sign up to set email alerts
|

Unregulated Expression of the Imprinted Genes H19 and Igf2r in Mouse Uniparental Fetuses

Abstract: The present study shows that the H19 and Igf2r genes, which are imprinted and expressed solely from maternal alleles, are expressed in an unregulatable manner in mouse uniparental, androgenetic, and parthenogenetic fetuses at day 9.5 of gestation. In the androgenetic fetuses, the H19 and Igf2r genes were respectively expressed at 12 and 40% of the levels in biparental fetuses. In addition, the expression of both genes was excessive (1259 and 482%, respectively) in the parthenotes. These expressions of the impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 37 publications
4
31
0
Order By: Relevance
“…Polyadenylated molecular species comprise the vast majority of intergenic RNAs in yeast (David et al 2006) and are also abundant in mammals (Kapranov et al 2007;Guttman et al 2009). Tour-de-force molecular dissection experiments have studied the regulatory function of a number of long, polyadenylated noncoding RNAs (Brannan et al 1990;Brown et al 1991;Lee et al 1999;Sotomaru et al 2002;Martens et al 2004;Willingham et al 2005;Hongay et al 2006;Camblong et al 2007;Rinn et al 2007;Thompson and Parker 2007;Uhler et al 2007;Houseley et al 2008). Such regulators exert their effects by a range of mechanisms, from cis-acting repression via transcription interference, as with the antisense regulator of the yeast meiosis factor IME4 (Hongay et al 2006), to trans-acting interactions with protein factors, as observed for the human noncoding transcript NRON, a nuclear trafficking regulator (Willingham et al 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyadenylated molecular species comprise the vast majority of intergenic RNAs in yeast (David et al 2006) and are also abundant in mammals (Kapranov et al 2007;Guttman et al 2009). Tour-de-force molecular dissection experiments have studied the regulatory function of a number of long, polyadenylated noncoding RNAs (Brannan et al 1990;Brown et al 1991;Lee et al 1999;Sotomaru et al 2002;Martens et al 2004;Willingham et al 2005;Hongay et al 2006;Camblong et al 2007;Rinn et al 2007;Thompson and Parker 2007;Uhler et al 2007;Houseley et al 2008). Such regulators exert their effects by a range of mechanisms, from cis-acting repression via transcription interference, as with the antisense regulator of the yeast meiosis factor IME4 (Hongay et al 2006), to trans-acting interactions with protein factors, as observed for the human noncoding transcript NRON, a nuclear trafficking regulator (Willingham et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, detailed single-locus studies have revealed regulatory function by long and polyadenylated species (Brannan et al 1990;Brown et al 1991;Lee et al 1999;Sotomaru et al 2002;Martens et al 2004;Willingham et al 2005;Hongay et al 2006;Camblong et al 2007;Rinn et al 2007; Thompson and Parker 2007;Uhler et al 2007;Houseley et al 2008). Genome-scale studies have identified characteristics of potential function at thousands of novel noncoding RNAs, including proximity to coding genes (Kapranov et al 2007;Xu et al 2009) and conservation across species (Guttman et al 2009), suggesting that many additional biologically active RNAs remain to be uncovered (Mattick 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Lack of silencing of imprinted genes in uniparental fetuses suggests that for some imprinted genes, the presence of both parental genomes is required for allele-specific control of expression. [80][81][82] Although we have only examined a small proportion of known imprinted loci, our findings suggest that there is considerable flexibility or tolerance in relation to variations in imprinted gene expression and methylation in the hematopoietic system of the adult.…”
Section: Imprinting In Uniparental Hematopoietic Cellsmentioning
confidence: 99%
“…Therefore, the disrupted expression of these maternally imprinted genes may explain why our pES cells exhibit normal growth and differentiation properties. In addition to the genes mentioned above, there are other reports about the disruption of specific expression of imprinted genes in uniparental fetuses and embryonic stem cells [37]. However, the mechanisms for the disruption remain largely unknown.…”
mentioning
confidence: 99%